MEMBANGUN KISAH INSPIRATIF PENERAPAN KEPUTUSAN DALAM ETIKA MORAL KRISTEN - Della Sari Manalu; Irfan Martin Pasaribu; Damayanti Nababan (Jurnal Ilmiah Multidisiplin Ilmu, 2024)
The objective of this research is to create a touching narrative about how Christians apply moral ethics in their lives across various situations and contexts. There is a fundamental difference between Christian ethics and general ethics. Christian ethics refer to moral values believed to originate from God, whereas ethics in the general philosophical sense regard moral values as derived from human reasoning and cultural reconstruction. Each individual needs to understand the dilemmas they face in making life decisions and how they can overcome these dilemmas. This research employs a qualitative methodology with a case study approach. Field research results indicate that decision-making is considered an art because it often involves a series of events with unique characteristics. This art of decision-making is always related to the goals to be achieved, the type of problems faced, and the influencing environmental factors. In the decision-making process, there are six views of decision-making: antinomianism, generalism, situationism, total absolutism, conflicting absolutism, and graded absolutism.